Impact of gas formation on the transfer of Ti and O from TiO2-bearing basic-fluoride fluxes to submerged arc welded metals: A thermodynamic approach. (December 2020) - Zhang, Jin; Coetsee, Theresa; Basu, Somnath; Wang, Cong
Abstract: Gas-slag-metal equilibrium calculations are performed to investigate the transfer of Ti and O to submerged arc welded metals with increasing TiO2 addition in basic-fluoride fluxes. The results indicate that activities of TiO2 and Ti2 O3 considering slag-metal reactions alone do not account for Ti transfer behaviors since TiF3 gas tends to form and reduce Ti-oxide activities. Thermodynamic simulation indicates that consideration of gases is essential to improve the prediction accuracy of Ti and O concentrations.